Efektifitas Buku Panduan Pembelajaran Kebencanaan Terhadap Peningkatan Hasil Belajar Siswa Pada Bencana Gempa Bumi Melalui Strategi Talking Stick Di SMA Negeri 1 Karanganom - Cahyanti, Elina; , Drs. Rubino Rubiyanto,M,Pd (2016)
Implementation of the strategy Talking Stick in this study aims to describe the effectiveness of teaching materials on disaster learning guide books Klaten regency in the earthquake indicated material by improving student learning outcomes. The study was conducted in SMA Negeri 1 Karanganom at Jl. Kingdom 3 Karanganom. Central Java. The method used in this study is an experiment with the design of the Pre-Test and Post-Test Coontrol Group Design. The selected sample is class X MIPA one of 27 students as control class and the class X MIPA 3 of 30 students as the experimental class. Learning strategies used in the classroom Konvensioanal control strategy, whereas the experimental class using the strategy with the Talking Stick data retrieval through about Pre-Test and Post-Test given to two classes. Teknikanalisis data used are Paired sample t-test to determine whether there are differences in the results. The tabulated results obtained showed that an increase in student learning outcomes in the control class from 60 to 84 and the experimental class of 62 to 86 can be concluded that book learning guides on disaster Klaten district effectively used, shown by the increasing student learning outcomes through strategies Talking Stick larger than on conventional strategy that is increased by 24. Keywords: teaching materials, improving student learning outcomes, strategies Talking Stick.